Collaborative learning and knowledge building in a mathematics teacher educator professional learning community in Ghana - Nkrumah, Frank Kwarteng (University of the Witwatersrand, Johannesburg, 2025)
This study investigates how collaborative professional learning experiences support the development of Mathematics Teacher Educators’ (MTEs’) knowledge and practices for teaching mathematics in pre-service teacher education in Ghana. Despite the critical role MTEs play in shaping future mathematics teachers, their own professional development needs and the specific knowledge required for their work remain underexplored, particularly in developing educational contexts. This research utilised a qualitative case study approach with data collection occurring in two phases: March to May 2022 and February to April 2023, following ethical clearance. Phase One examined collaborative practices within a Professional Learning Community (PLC) of MTEs from one teacher education institution in Ghana, while Phase Two explored the role of critical friendships in supporting MTEs’ professional growth. Grounded in sociocultural learning theory, the study integrated Desimone’s framework for effective continuous professional development, Wenger’s dimensions of practice, and McCrory et al.’s knowledge of algebra for teaching framework as lenses through which data was analysed in the two phases. Data collection methods included PLC observations, focus group interviews with MTEs, individual interviews with MTEs and their critical friends, and classroom observations of MTEs’ teaching practice. The analysis involved both deductive and inductive thematic approaches, employing the theoretical frameworks to examine collaborative learning dynamics and knowledge development among MTEs. Key findings reveal that content-focused and domain-specific professional learning are crucial for MTEs’ development, supporting findings from prior research. The study identified three core knowledge domains vital for MTEs: Pedagogical content knowledge, subject-matter knowledge, and knowledge of educational contexts. Collaborative learning within PLCs and critical friendships were found to enhance MTEs’ professional knowledge and practices substantially, fostering reciprocal expertise development and catalysing pedagogical innovation. The study also highlighted the complex, specialised nature of knowledge required for teaching teachers, extending beyond what is typically considered for school-level mathematics teaching. However, challenges were noted in translating collaborative learning into individual classroom practices, including time constraints and varying levels of participation and commitment of MTEs in the PLC activities, which led to uneven professional growth. This research contributes to the field by providing an integrated theoretical framework for understanding MTE professional development, offering methodological innovations in studying critical friendships, and identifying specific knowledge domains crucial for MTEs. The findings have substantial implications for policy and practice in mathematics teacher education, suggesting the need for sustained, collaborative professional development models and curriculum reforms in MTE preparation programs. While contextualised in Ghana, the study offers insights relevant to the broader international discourse on mathematics teacher education, particularly in developing educational contexts. It opens avenues for future research on the longitudinal impacts of MTE professional development, cross-cultural comparisons, and the scaling of successful collaborative learning models in diverse educational settings.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2025
Keywords: Mathematics teacher education; Professional learning; Professional learning community; Mathematical knowledge for teaching teachers; Pre-service teachers; Critical friendships; Collaborative learning; Professional practices; UCTD; SDG-4: Quality education; SDG-10: Reduced inequalities